Green-synthesized silver nanoparticles from black elderberry extract as potential TMPRSS2 inhibitors: Implications for SARS-CoV-2 antiviral therapeutics - Tavukcuoglu, Ozlem; Ciftci, Fatih; Duygulu, Nilufer Evcimen; Misirli, Duygu; Elmastas, Mahfuz; Isildak, Ibrahim (ELSEVIER, 2025)
This study investigates the green synthesis and characterization of silver nanoparticles (AgNPs) derived from black elderberry (Sambucus nigra) (BE) extract. A primary focus is their inhibitory effect on Transmembrane Serine Protease 2 (TMPRSS2), a host enzyme that facilitates viral entry, including that of SARS-CoV-2. BE_AgNPs were synthesized using elderberry extract as a reducing and stabilizing agent and characterized through UV-Vis spectroscopy, dynamic light scattering (DLS), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), transmission electron microscopy (TEM), and high-resolution TEM (HRTEM). Antibacterial activity was tested against Escherichia coli, cytotoxicity was assessed using XTT assays on L929 cells, and TMPRSS2 inhibition was evaluated via a fluorometric enzyme assay. The synthesized BE_AgNPs exhibited a mean particle size of 17.62 +/- 4.91 nm and showed potent antibacterial activity with a 23.11 +/- 0.35 mm inhibition zone. XTT assays confirmed > 80 % cell viability across all tested concentrations. In TMPRSS2 inhibition assays, BE_AgNPs demonstrated dose-dependent activity, reaching 46.88 % inhibition at 100 & micro;g/mL. Although less potent than the positive control Camostat, BE_AgNPs likely inhibit TMPRSS2 via non-covalent interactions. The findings indicate that green-synthesized BE_AgNPs are multifunctional nanomaterials with potential therapeutic applications in the treatment of viral infections and secondary bacterial complications.
Keywords: Black elderberry; Green synthesis; TMPRSS2; SARS-CoV-2; Silver nanoparticles; ANTIMICROBIAL ACTIVITY; ANTIOXIDANT; Materials Science